Influence of neutron irradiation and annealing on the optical properties of GaN - Rodrigues, J.
Epitaxial GaN layers were irradiated with fast and thermal neutrons in the Portuguese Research Reactor. Irradiation leads to a quenching of the typical GaN near band edge and yellow luminescence for samples excited with above band gap photon energy. Although structural techniques indicate a full recovery of irradiation damage for annealing at 1000 ºC, the near band edge emission is not recovered after annealing. Nevertheless, deep level recombination is detected with above and below band gap excitation. In particular, the yellow and green luminescence bands (at 2.2 and 2.35 eV) are observed upon above band gap excitation while under illumination with below the band gap energy a yellow luminescence at 2.1 eV and infrared unstructured bands at 1.2 eV and 1.0 eV are observed The position of below gap broad bands is strongly dependent on the irradiation conditions and annealing pointing to the formation of distinctly different defect complexes or different charge states of optically active defects.